Proteomics analysis of cells incubated with R-enantiomer of warfarin, an anti-coagulating drug - Teo, Kathrine Wei Shi. (2009)
Proteomics analysis of individual chiral drugs is a relatively novel idea in the research field and although warfarin is a standard anticoagulant and widely used in medical field, its narrow therapeutic range makes it hard to determine an accurate dosage. This study thus aims to provide a better understanding and perspective of warfarin and reduction of its potential side effects. Subcultured HepG2 liver cells were treated with 20uM of warfarin and the cytotoxicity level of warfarin was determined by MTT assay. Sample of cells treated with warfarin was then labeled with iTRAQTM Reagents 117 (for R-warfarin) before injecting into iTRAQ-coupled two dimension liquid chromatographymass spectrometry (LC/MS-MS). Control cells treated with no drug were labeled with iTRAQ 114. iTRAQ analysis identified 350 unique proteins based on evaluative criteria (cutoff protein score of more than 2). Up or down regulation of the proteins were further analysed using online Swiss-Prot database. Since these proteins induce cellular change towards warfarin, they may be related to the action of warfarin drug. As supported by previous literature reviews, R-warfarin was found to be less active than Swarfarin.